Insoluble dendrimer-grafted poly(vinylimidazole) microbeads stabilized with mono/bimetallic nanoparticle catalysts for effective degradation of malachite green. (1st September 2017) - Murugan, Eagambaram; Nimita Jebaranjitham, J.; Janaki Raman, K.; Mandal, Abhishek; Geethalakshmi, D.; Dharmendira Kumar, M.; Saravanakumar, A.
Abstract : Six types of heterogeneous nanoparticle catalysts viz., insoluble Poly-VIm beads grafted with D(G2) & D(G3) PPI dendrimers stabilized/immobilized with AuNPs/AuPdNPs were prepared by varying the cross-linking load as 2% (LC) and 10% (HC) and demonstrated the same as superior catalysts for effective reduction of Malachite Green. Abstract : Six types of insoluble bead-shaped stable heterogeneous nanoparticle catalysts were prepared using two categories of poly( N -vinylimidazole) microbeads grafted with D(G2) and D(G3) matrices derived from 2% (LC) and 10% (HC) cross-linking monomer load, viz., divinylbenzene, followed by individual stabilization/immobilization of AuNPs/AuPdNPs. All these catalysts were characterized using FT-IR, UV-Vis, SEM, EDAX, XRD and TGA analyses. These catalysts were individually employed for the degradation of malachite green as a model reaction under pseudo first-order condition. Among the bimetallic catalysts, LC-PVIm-D(G3)–AuPdNP (36.61 × 10 −3 min −1 ) was shown to be superior; specifically, it was three times more active than the monometallic catalyst, LC-PVIm-D(G2)–AuNP (11.35 × 10 −3 min −1 ). Hence, the superior catalyst was employed for detailed kinetic studies by varying the [substrate], [NaBH4 ] and [catalyst], and each experimental parameter was found to influence the reaction. The recycling efficiency of this superior catalyst was studied five times, and the activity was found to remain unaltered even at the fifth cycle, and hence, the catalyst was stable and suitable to carry out the reduction reaction in the logistic mode.